Development of a scanning soft X‐ray spectromicroscope to investigate local electronic structures on surfaces and interfaces of advanced materials under conditions ranging from low vacuum to helium atmosphere. (18th March 2020) - Oura, Masaki; Ishihara, Tomoko; Osawa, Hitoshi; Yamane, Hiroyuki; Hatsui, Takaki; Ishikawa, Tetsuya
Abstract : The development of a scanning soft X‐ray spectromicroscope is described. Abstract : A scanning soft X‐ray spectromicroscope was recently developed based mainly on the photon‐in/photon‐out measurement scheme for the investigation of local electronic structures on the surfaces and interfaces of advanced materials under conditions ranging from low vacuum to helium atmosphere. The apparatus was installed at the soft X‐ray beamline (BL17SU) at SPring‐8. The characteristic features of the apparatus are described in detail. The feasibility of this spectromicroscope was demonstrated using soft X‐ray undulator radiation. Here, based on these results, element‐specific two‐dimensional mapping and micro‐XAFS (X‐ray absorption fine structure) measurements are reported, as well as the observation of magnetic domain structures from using a reference sample of permalloy micro‐dot patterns fabricated on a silicon substrate, with modest spatial resolution ( e.g. ∼500 nm). Then, the X‐ray radiation dose for Nafion ® near the fluorine K ‐edge is discussed as a typical example of material that is not radiation hardened against a focused X‐ray beam, for near future experiments.